PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI SMK SIERE CENDEKIA - Diah Ayu Septianingsih; Dede Andi (Journal of Research and Publication Innovation, 2025)
This study aims to determine the effect of leadership style on the performance of SMK Siere Cendekia employees. To determine the effect of work motivation on the performance of SMK Siere Cendekia employees and to determine how the influence of leadership style and work motivation on the performance of SMK Siere Cendekia employees. This research method uses a quantitative associative method. Data collection techniques in this study used observation and questionnaire techniques. Data obtained by questionnaires with a total of 52 employees. Leadership style has a significant effect on employee performance. This is evidenced by the regression equation obtained, namely Y = 9.348 + 0.786X1. The correlation coefficient value of 0.702 indicates that the two variables have a strong relationship, with a determination coefficient of 49.3%. Based on the hypothesis test, tcount> ttable is obtained, namely (6.976> 1.677) and a significant value of 0.000 <0.05. Work motivation has a significant effect on employee performance. This is evidenced by the regression obtained Y = 4.866 + 0.880X2. The correlation coefficient value of 0.926, indicates that the two variables have a strong relationship, with a determination coefficient of 85.7%. Based on the hypothesis test, tcount> ttable is obtained, namely (17.294> 1.677) and a significant value of 0.000 <0.05. Leadership Style and Work Motivation have a significant influence on employee performance. This is evidenced by the regression obtained Y = 4.578 + 0.024 (X1) + 0.865 (X2). The correlation coefficient value of 0.926 indicates that the independent variable and the dependent variable have a strong relationship, with a determination coefficient of 85.7%. Based on the hypothesis test, the Fcount value> Ftable is (146.792> 3.19) with a significant value of 0.000 <0.05. Thus, Ho3 is rejected, and Ha3 is accepted, which means that there is a significant influence between Leadership Style and Work Motivation on Employee Performance.